Benzene tricarboxamide derivatives with lipid and ethylene glycol chains self-assemble into distinct nanostructures driven by molecular packing. Issue 67 (2nd August 2021) - Aljuaid, Nada; Tully, Mark; Seitsonen, Jani; Ruokolainen, Janne; Hamley, Ian W.
Abstract : The self-assembly in aqueous solution of benzene-1, 3, 5-tricarboxamide (BTA) bearing one alkyl chain and two PEG (polyethylene glycol) chains or two alkyl chains and one PEG chain yields molecular-packing driven nanostructures. Abstract : The self-assembly in aqueous solution of benzene-1, 3, 5-tricarboxamide (BTA) bearing one alkyl chain and two PEG (polyethylene glycol) chains or two alkyl chains and one PEG chain yields completely distinct nanostructures. Two series of derivatives were synthesized and extensively characterized and electron microscopy and small-angle X-ray scattering (SAXS) reveal micelle structures for derivatives with one alkyl and two PEG chains, but nanotapes and nanoribbons for the series with two alkyl and one PEG chain.